2007
DOI: 10.1111/j.1365-2052.2007.01664.x
|View full text |Cite
|
Sign up to set email alerts
|

Genes affecting coat colour and pattern in domestic dogs: a review

Abstract: Tremendous progress has been made in identifying genes involved in pigmentation in dogs in the past few years. Comparative genomics has both aided and benefited from these findings. Seven genes that cause specific coat colours and/or patterns in dogs have been identified: melanocortin 1 receptor, tyrosinase related protein 1, agouti signal peptide, melanophilin, SILV (formerly PMEL17), microphthalmia-associated transcription factor and beta-defensin 103. Although not all alleles have been yet identified at eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 53 publications
(72 reference statements)
2
114
0
5
Order By: Relevance
“…In contrast to the expansion and diversification of the ␣-defensin proteomes, the organization of ␤-defensin gene clusters is much more highly conserved and the primary structures of certain ␤-defensin peptides exhibit similarities across phylogenetic lines (41,42,57,65). The molecular basis of this disparity remains unknown, but perhaps it relates to receptor-mediated roles that have been identified for members of the ␤-defensin peptide family (4,7,15,49,(62)(63)(64). In contrast to the more centromeric ␣-defensin gene locus (Fig.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast to the expansion and diversification of the ␣-defensin proteomes, the organization of ␤-defensin gene clusters is much more highly conserved and the primary structures of certain ␤-defensin peptides exhibit similarities across phylogenetic lines (41,42,57,65). The molecular basis of this disparity remains unknown, but perhaps it relates to receptor-mediated roles that have been identified for members of the ␤-defensin peptide family (4,7,15,49,(62)(63)(64). In contrast to the more centromeric ␣-defensin gene locus (Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Bottleneck processes, but selective sweeps also, have been important in domestication. It is, however, relevant to mention that humans, by breeding fancy phenotypes that would otherwise have been removed in the wild by natural selection, has also maintained deleterious alleles at high frequencies (Fang et al, 2009;Ludwig et al, 2009;Schmutz and Berryere, 2007). Overall, however, little is known so far on the precise molecular history and of the effects of artificial selection in livestock, including the species studied here, the pig.…”
Section: Introductionmentioning
confidence: 96%
“…A previous observation indicated that the white body color might be conditioned by a single gene which is completely dominant to gray, and is partially dominant or epistatic to black, while black is completely dominant or epistatic to gray [1]. Until now, there are no genes reported to correlate with the coat color in buffalo, although the genetic mechanism of coat color has been extensively investigated in other animals [2][3][4][5][6][7][8][9].…”
mentioning
confidence: 98%